Design of preclinical studies of biomedical cell products: characteristics, key principles and requirements - E. V. Melnikova; O. V. Merkulova; A. A. Chaplenko; V. A. Merkulov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
According to the Federal Law «On Biomedical Cell Products», preclinical trials are an integral part of biomedical cell product (BCP) development. This article describes the basic principles of fulfilling requirements laid down in the Rules for conducting preclinical trials of BCPs. The main objective of preclinical trials is evaluation of efficacy, safety and biodistribution of cell products. Properly justified markers of biological activity must be used for reliable identification of BCP pharmacodynamic action in the host organism. BCP safety assessment must be comprehensive and include identification, characterization and quantitative evaluation of potential local and systemic toxicity, estimation of the onset of toxicity and possibility of its reduction, and the effect of a particular drug dose on the results of toxicity studies. The ultimate goal of preclinical toxicity studies is to obtain data sufficient for making a conclusion on the possibility of conducting clinical trials of BCP and determining associated risks. The key principles of preclinical trials design are a rational approach and justification of all decisions made during the study. The results of preclinical trials that were conducted in compliance with the law, can be included in the BCP dossier and considered during the product authorization by the expert institution of the Ministry of Health.